St. Anns Road, looking South, Port of Spain, Trinidad - (:unkn) unknown (My University, 2010)
The postcard shows the road to St.Anns which is located on the southern side of the Queen's Park Savannah.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Queen's Park Savannah; Savannas; Cities and towns--St. Ann's